(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the effects of different tryptophan and digestible lysine ratios for growing Japanese quails (1 to 40 days of age) with repercussions on the early stage of production (41 to 110 days of age). A total of 1000 one day old Japanese quails were distributed at random, with five tryptophan and digestible lysine ratios, 10 replicates and 20 birds per experimental unit. A tryptophan- deficient basal diet was formulated with 1.48 g of digestible tryptophan /kg, corresponding to a ratio of tryptophan and lysine of 0.14. This basal diet was supplemented with five levels of L-tryptophan (98%), replacing glutamic acid corresponding to the tryptophan and lysine ratio of 0.14 (no supplementation); ratios of 0.16; 0.18; 0.20 and 0.22, being the diets isocaloric and isonitrogenous. The performance of the birds in the growing and egg laying phases was evaluated. Although body weight and weight gain until 40 days of age had increased (P<0,001) and feed intake in the egg laying phase had decreased (P=0,037) in a linear fashion, LRP was the one with the best adjustment for those parameters. The effect was quadratic for feed intake (P=0,0069), feed conversion (P=0,0032) and viability (P<0,001) of the birds in the growing phase. A quadratic effect was found for egg production per bird housed at one day of age (P<0,001), weight gain at 110 days of age (P=0,039) and feed conversion per egg mass (P=0,046) in the laying phase. Intake of tryptophan increased (P<0,001) and egg production per housed bird in the laying phase linearly decreased (P<0,001) with the increase in the ratios between tryptophan and lysine. The digestible tryptophan and digestible lysine ratio is 0.18 (1.88 g of tryptophan/kg and 10.5 g of lysine/kg of diet), corresponding to an intake of 20.63 mg of tryptophan per bird per day, in the diet for growing, provides greater viability of birds in the growing phase and a satisfactory performance of Japanese quails in the laying phase.